2017
DOI: 10.1097/md.0000000000007909
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms in TLR2 and TLR4 with asthma risk

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
1
22
0
1
Order By: Relevance
“…This has been associated with the risk of asthma (but not rhinoconjunctivitis), 5 but not replicated in another survey, 6 or in a meta-analysis of 14 different studies. 3 This TLR4 hyporesponsiveness to LPS and asthma risk is consistent with the notion that microbial multiplicity and exposure to high levels of LPS mitigate against the development of allergy. [7][8][9] The PARSIFAL study demonstrated that maternal exposure to microbes from farms increased the expression of TLR4 and CD14 (a coreceptor of the TLR4 signalling pathway) in children from farming communities and this was associated with a reduction in the development of allergic disease.…”
Section: Hdm Allerg En S and Toll-like Recep To R Ssupporting
confidence: 79%
“…This has been associated with the risk of asthma (but not rhinoconjunctivitis), 5 but not replicated in another survey, 6 or in a meta-analysis of 14 different studies. 3 This TLR4 hyporesponsiveness to LPS and asthma risk is consistent with the notion that microbial multiplicity and exposure to high levels of LPS mitigate against the development of allergy. [7][8][9] The PARSIFAL study demonstrated that maternal exposure to microbes from farms increased the expression of TLR4 and CD14 (a coreceptor of the TLR4 signalling pathway) in children from farming communities and this was associated with a reduction in the development of allergic disease.…”
Section: Hdm Allerg En S and Toll-like Recep To R Ssupporting
confidence: 79%
“…29 The lack of association between the TLR4/+896A/G polymorphism and asthma has also been confirmed by the latest metaanalysis. 23 In contrast, a previous meta-analysis of 8 studies showed a marginal association of TLR4/+896A/G with asthma risk, indicating that the major A allele might protect against asthma. 24 This is in agreement with a study among Swedish children suggesting that the AG genotype was associated with an increased risk of asthma, especially atopic asthma.…”
Section: Discussionmentioning
confidence: 88%
“…Among the reported studies, most found that these polymorphisms were associated with asthma and allergic diseases, though the reports are contradictory. [22][23][24][25] In the ALEX study, the wild-type TLR2/-16934T allele was found to be associated with fewer asthma diagnoses, symptoms and atopy among German and Austrian farmers' children, but this relationship was not observed in children who did not live on a farm. 26 The TLR4/+896A/G variant was found to be associated with 4-fold higher prevalence of asthma and a 7-fold higher prevalence of atopic asthma in a population of Swedish children.…”
Section: Introductionmentioning
confidence: 95%
“…4,27 Two functional missense SNPs (Single Nucleotide Polymorphism) in the coding sequence of TLR4 gene are rs4986790 (A + 896G, Asp299Gly) and rs4986791 (C + 1196T, Thr399Ile), with linkage disequilibrium, modify the extracellular domain of the corresponding protein and lead to a different LPS responsiveness. 28 The recent meta-analysis studies have suggested the effects of TLR4 polymorphisms on susceptibility to various diseases such as Open Angle Glaucoma (rs1927911, rs2149356, rs4986791, rs7037117, and rs10759930), 29 cancers (rs4986790 and rs4986791), 30,31 Pneumonia (rs4986790), 32 Asthma (rs4986791), 33 Crohn's disease (rs4986791), 34 and Atopic Dermatitis (rs4986790). 35 IL-8 as an important chemotactic cytokines has a high level of productions in the nAMD patient's PBMCs and RPE cells.…”
Section: Discussionmentioning
confidence: 99%